Regenerated kenaf core cellulose hydrogels and films prepared via pre-cooled method / Adam Khairul Faiz ... [et al.] - Khairul Faiz, Adam; Ismail, Muhammad Khairil Hakim; Kaco, Hatika; Sajab, Mohd Shaiful (2021)
Hydrogels are an emerging technology in the agriculture industry. Hydrogel refers to water- retention granule because of its ability to swell to many times its original size when it encounters water. The aims of this study are to extract cellulose from kenaf and investigate the properties of the produced regenerated cellulose hydrogel and film. The kenaf underwent bleaching and alkali treatment processes to extract the cellulose. Consequently, the kenaf cellulose extracted was dissolved in alkaline/urea solvent to form a transparent cellulose solution. This solution was separated into two parts. One part was used to form cellulose hydrogel by adding crosslinker and the other part was used to form cellulose film through the coagulation process. The average viscosity molecular weight of kenaf cellulose measured using Ubbelohde viscometer was 1.7 x 105. Meanwhile, the dissolution of kenaf cellulose shows the long cellulose chains becomes shorter. The FTIR result shows that kenaf was successfully extracted to form cellulose where the cellulose functional groups appeared on the spectrum. In addition, the transparency of cellulose hydrogel is higher compared to cellulose film due to the high porosity of cellulose hydrogel compared to closed surface porosity of cellulose film revealed from the morphological study.